2018
DOI: 10.5194/amt-11-4509-2018
|View full text |Cite
|
Sign up to set email alerts
|

The importance of surface reflectance anisotropy for cloud and NO<sub>2</sub> retrievals from GOME-2 and OMI

Abstract: The angular distribution of the light reflected by the Earth's surface influences top-of-atmosphere (TOA) reflectance values. This surface reflectance anisotropy has implications for UV/Vis satellite retrievals of albedo, clouds, and trace gases such as nitrogen dioxide (NO 2 ). These retrievals routinely assume the surface to reflect light isotropically. Here we show that cloud fractions retrieved from GOME-2A and OMI with the FRESCO and OMCLDO2 algorithms have an east-west bias of 10 % to 50 %, which are hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
66
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(77 citation statements)
references
References 38 publications
10
66
1
Order By: Relevance
“…In Fig. 4 The deviations found over land are in line with conclusions from a recent study by Lorente et al (2018), who showed that traditional Lambertian surface albedo databases, like the ones described in Sect. 3.4, seriously underestimate the surface reflectivity for certain geometries due to the fact that surface reflectance anisotropy is not accounted for in these databases.…”
Section: Surface Albedo Errorssupporting
confidence: 90%
See 1 more Smart Citation
“…In Fig. 4 The deviations found over land are in line with conclusions from a recent study by Lorente et al (2018), who showed that traditional Lambertian surface albedo databases, like the ones described in Sect. 3.4, seriously underestimate the surface reflectivity for certain geometries due to the fact that surface reflectance anisotropy is not accounted for in these databases.…”
Section: Surface Albedo Errorssupporting
confidence: 90%
“…Adopting Lambertian surface reflection can cause errors especially for the longer wavelengths. For example, neglect of the directional dependence can lead to errors of a factor of two or more in the surface reflectance of vegetated surfaces (Lorente et al, 2018).…”
Section: Surface Albedo Inputmentioning
confidence: 99%
“…An improved V2.0 DOMINO retrieval (Boersma et al, 2011) algorithm reduced the retrieval errors while increasing the estimated air mass factor, which reduces the retrieved TCNO 2 by up to 20 % in winter and 10 % in summer. The current versions of OMNO2-NASA (Krotkov et al, 2017) and v2.0 DOMINO (Boersma et al, 2011) are generally in good agreement (Marchenko et al, 2015;Zara et al, 2018). However, the OMNO2-NASA TCNO 2 retrievals are 10 % to 15 % lower than the v2.0 DOMINO retrievals and with Quality Assurance for Essential Climate Variables (QA4ECV) retrievals.…”
Section: Introductionmentioning
confidence: 75%
“…Enhanced agreement with OMI retrievals revised using observed NO 2 profiles is indicative of retrieval errors from model-based a priori vertical NO 2 profile shapes (Figure 8(d-f), Table A3), and highlights the need of approaches to address the issue. Moreover, improved accuracy in other retrieval parameters, both surface and atmospheric, help enhance the quality of satellite NO 2 retrievals (Laughner et al, 2019;Vasilkov et al, 2017Vasilkov et al, , 2018Lorente et al, 2018;Lin et al, 2014Lin et al, , 2015Liu et al, 2019;Noguchi et al, 2014;Zhou et al, 2011) 4 Conclusions…”
Section: Assessment Of Omi No 2 Retrievalsmentioning
confidence: 99%